Nonmetal high-temperature-resistant temperature-sensing optical cable
Through the non-metallic high-temperature temperature-sensitive optical cable designed with a multi-layer composite structure, the problem of degradation of existing optical cables in high-temperature environments is solved, stable operation and accurate temperature measurement at high temperatures are achieved, and the needs of high-temperature temperature monitoring are met.
Patent Information
- Application Number
- CN202510208176.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-25
AI Technical Summary
Existing optical cables are prone to deformation and oxidation in high-temperature environments, resulting in degradation of signal transmission performance and it is difficult to meet the requirements of accurate temperature measurement and real-time monitoring in high-temperature environments.
Non-metallic high-temperature temperature-resistant optical cables designed with multi-layer composite structures include high-temperature fibers, tight cladding, high-temperature protection parts, inner sheath and outer sheath. The tight cladding uses polyimide composite material, the high-temperature resistant protective parts are filled with aluminum silicate aerogel with polytetrafluoroethylene corrugated pipe, and the inner cover is made of composite boron nitride nanotubes, graphene oxide, silicon carbide whiskers and other materials. The outer sheath is three-dimensionally woven by aramid, modified silicon carbide fibers and polytetrafluoroethylene fibers.
The stable operation of optical cables at long-term and short-term high temperatures of 200℃ and 250℃-300℃ has been achieved, which significantly improves the high temperature resistance, corrosion resistance and mechanical damage resistance of optical cables, and meets the needs of high-temperature temperature monitoring.
Smart Images

Figure CN119828306A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables and relates to a non-metallic high-temperature-resistant temperature-sensitive optical cable. Background Art
[0002] Optical cable is a light transmission tool that uses the principle of total reflection of light in glass or plastic fibers. It consists of optical fiber, plastic protective sleeve and plastic sheath. It plays an extremely critical role in modern communication networks, enabling high-speed, large-capacity data transmission. It is widely used in telecommunications, the Internet, cable television and many other fields, providing a stable and reliable physical channel for the rapid dissemination of information.
[0003] With the continuous development of industry, in some special working environments, such as petrochemical, steel smelting, electric power and other high-temperature working scenes, conventional optical cables cannot meet the needs. These environmental temperatures are often as high as several hundred degrees Celsius or even higher. The metal materials in ordinary optical cables are prone to deformation and oxidation at high temperatures, resulting in degradation or even interruption of signal transmission performance. At the same time, metal materials may also cause electromagnetic interference and affect the accuracy of the signal. Therefore, in order to meet the communication and monitoring needs in these extreme high-temperature environments, the development of non-metallic high-temperature resistant temperature-sensing optical cables has become an inevitable trend. This type of optical cable must not only have good high-temperature resistance, but also be able to accurately sense temperature changes to ensure the safe and stable operation of related equipment and systems.
[0004] However, the existing technology for preparing non-metallic high-temperature resistant temperature-sensitive optical cables has some shortcomings. On the one hand, in terms of material selection, although some non-metallic materials have certain high-temperature resistance, their physical and chemical properties will still change slowly under the long-term action of high temperature, resulting in the gradual deterioration of the mechanical and optical properties of the optical cable, affecting the service life. On the other hand, in terms of temperature sensing technology, the accuracy and stability of existing temperature sensing elements and temperature sensing principles in high temperature environments need to be improved, and it is difficult to meet the stringent requirements for accurate temperature measurement and real-time monitoring. In addition, the preparation process is also relatively complex and the cost is high, which to a certain extent limits the large-scale application and promotion of non-metallic high-temperature resistant temperature-sensitive optical cables. Summary of the invention
[0005] The present invention relates to a non-metallic high-temperature resistant temperature-sensing optical cable, and belongs to the field of cable technology. The present invention adopts a multi-layer composite structure design, with the high-temperature resistant optical fiber as the center, and sequentially wraps a tight cladding, a high-temperature resistant protective part, a high-temperature resistant inner protective layer and a high-temperature resistant outer sheath. The tight cladding adopts a polyimide composite material to enhance the thermal stability and mechanical strength of the optical fiber; the high-temperature resistant protective part uses a polytetrafluoroethylene corrugated tube filled with aluminum silicate aerogel to improve the heat insulation and high-temperature resistance; the inner protective layer material provides excellent mechanical properties and corrosion resistance by composite boron nitride nanotubes, graphene oxide, silicon carbide whiskers and other high-performance fillers; the outer sheath is three-dimensionally woven by aramid fiber, modified silicon carbide fiber and polytetrafluoroethylene fiber, which greatly enhances the tensile strength and impact resistance of the optical cable. This optical cable can be used in the field of high-temperature temperature sensing monitoring, and has multiple advantages such as high temperature resistance, corrosion resistance, and mechanical damage resistance.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A non-metallic high-temperature resistant temperature-sensitive optical cable, the center of the optical cable is a high-temperature resistant optical fiber, and the optical fiber is wrapped from the inside to the outside respectively: a tight cladding, a high-temperature resistant protective component, a high-temperature resistant inner protective layer, and a high-temperature resistant outer sheath.
[0008] As a preferred technical solution of the present invention, the tight cladding is a polyimide composite material; the preparation method of the polyimide composite material is: polyimide, nanographene and nanosilicon dioxide in a mass ratio of 70-80:1-3:10-20 are melt-blended at 300-350°C for 20-40 minutes to obtain the polyimide composite material.
[0009] As a preferred technical solution of the present invention, the high temperature resistant protective member is a polytetrafluoroethylene bellows filled with aluminum silicate aerogel composite material; the preparation method of the polytetrafluoroethylene bellows is: polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate are mixed evenly with a ball mill, added into a screw extruder, and melt blended according to the temperature gradient set at 340-360°C in the feeding section, 330-350°C in the mixing section, and 290-310°C in the base section, and a bellows with a diameter of 400-420 μm is extruded through a bellows die; the mass ratio of the polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate is 100:10-20:1.6-2.0:1.0-1.4;
[0010] As a preferred technical solution of the present invention, the preparation method of the high temperature resistant inner protective layer is as follows: dispersing boron nitride nanotubes and graphene oxide in N-methylpyrrolidone 35-45kHz ultrasound for 1-3h, placing silicon carbide whiskers in 0.5-2wt% silane coupling agent KH550 ethanol solution, adjusting the pH to 8-9 with ammonia water and ultrasonically stirring for 30-60min, and then washing and drying to obtain modified silicon carbide whiskers; polyetheretherketone, polyimide, boron nitride nanotubes , graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers are added into a twin-screw extruder, and the feeding section temperature is set to 330-350°C, the mixing section temperature is set to 370-390°C, and the extrusion section temperature is set to 350-370°C to obtain a high-temperature resistant inner protective layer material; the mass ratio of polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers is 6-7:3-4:1-5:0.5-2:5-10:5-10.
[0011] As a preferred technical solution of the present invention, the high temperature resistant outer sheath is woven from aramid, modified silicon carbide fiber and polytetrafluoroethylene fiber. The modified silicon carbide fiber is prepared by immersing the silicon carbide fiber in a 1-2% silane coupling agent KH550 anhydrous ethanol solution, ultrasonicating at 30-50°C for 30-60min, drying at 80-120°C for 10-14h, and further heat treating at 150-200°C for 30-60min.
[0012] Furthermore, the preparation of the non-metallic high temperature resistant temperature sensitive optical cable comprises the following steps:
[0013] (1) A modified polyimide coating with a thickness of 50±5μm was applied to a high temperature resistant optical fiber with a diameter of 250um, a wavelength of 365nm, and an intensity of 500mJ / cm 2 The ultraviolet curing treatment forms a tight cladding optical fiber;
[0014] (2) Passing the tight clad optical fiber through the corrugated tube, injecting the aluminum silicate gel composite material, treating it at a vacuum negative pressure of -0.08 MPa for 20-30 minutes to eliminate internal bubbles, placing it in a supercritical drying device, using liquid carbon dioxide as a drying medium, setting the temperature to 35-45° C., the pressure to 8-12 MPa, and drying it for 22-26 hours to obtain a corrugated tube high temperature resistant protective part of aluminum silicate aerogel with a nanoporous structure;
[0015] (3) placing the high temperature resistant inner protective layer material into the extruder, setting the feeding section temperature to 330-350°C, the mixing section temperature to 370-390°C, and the extrusion section temperature to 350-370°C, and uniformly coating the inner protective layer material on the outside of the high temperature resistant protective part to form a complete high temperature resistant inner protective layer with a moderate thickness of 0.5-1 mm;
[0016] (4) Aramid fiber, modified silicon carbide fiber, and polytetrafluoroethylene fiber are three-dimensionally woven in a mass ratio of 5-7:2-4:0.5-1.5, with a braiding angle of 58±2° and a braiding density of 120±5 strands / inch to form a high-temperature resistant outer sheath that is coated on the outer surface of the inner sheath to obtain a non-metallic high-temperature resistant temperature-sensitive optical cable.
[0017] As a preferred technical solution of the present invention, the preparation method of the aluminum silicate gel composite material in step (2) is: dissolving aluminum nitrate and sodium silicate in deionized water, adjusting the pH value to 3-5 with 1M dilute hydrochloric acid, stirring at 60-80°C for 2-4 hours to form a uniform aluminum silicate sol, then adding ammonia catalyst to the sol, adjusting the pH value to 6-8, promoting the transformation of the sol to gel, standing for 20-24 hours to gel the sol, immersing the gel in anhydrous ethanol for 8-12 hours and performing solution replacement 3-5 times to obtain the aluminum silicate gel composite material; the mass ratio of the aluminum nitrate, sodium silicate and deionized water is 1.5-2.0:1-1.5:20-30.
[0018] Beneficial effects of the present invention:
[0019] (1) The tight sheath of the present invention adopts a polyimide composite material, and the thermal stability and mechanical strength of the polyimide are enhanced by introducing nanographene and nanosilicon dioxide; the high temperature resistant protective part uses a polytetrafluoroethylene corrugated tube filled with aluminum silicate aerogel, and the polytetrafluoroethylene provides chemical stability and thermal resistance, while the aluminum silicate aerogel achieves excellent thermal insulation effect through its nanoporous structure. The overall structural design enables the optical cable to be used at a temperature of 200°C for a long time and can withstand a high temperature of 250°C-300°C in a short time.
[0020] (2) The inner sheath of the present invention is made of materials such as polyetheretherketone, polyimide and boron nitride nanotubes, which significantly improves the strength and wear resistance of the optical cable; the outer sheath adopts a three-dimensional braided structure of aramid, modified silicon carbide fiber and polytetrafluoroethylene fiber, and by optimizing the braiding angle and density, the tensile strength and mechanical impact resistance of the optical cable are significantly improved. In addition, the corrosion resistance and moisture and heat resistance of the material enable the optical cable to maintain stable operation in harsh environments.
[0021] (3) The present invention adopts a combination of multiple advanced processes and high-performance materials in the preparation process. The tight sheath is coated with modified polyimide by UV curing technology, which improves production efficiency and reduces environmental pollution; the high-temperature resistant protective part is processed by supercritical drying technology to treat aluminum silicate aerogel, which retains the high porosity characteristics of its nanostructure and improves the thermal insulation performance; the inner protective layer and outer sheath are made of twin-screw extrusion and three-dimensional weaving technology to achieve uniform dispersion of materials and structural optimization. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0023] Figure 1 This is the structural diagram of non-metallic high temperature resistant temperature sensitive optical cable. DETAILED DESCRIPTION
[0024] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0025] In the following embodiments and comparative examples, polyimide was purchased from EVONIK / Evonik brand flagship store with the brand name P84Fibre A HT; polytetrafluoroethylene was purchased from Langfang Xuanhui Sealing Material Co., Ltd.; aramid was purchased from Dongguan Sovit Special Wire and Tape Co., Ltd. with the product number 496921513; polytetrafluoroethylene fiber was purchased from Gemandi Textile Co., Ltd. with the product number GMD7; and silicon carbide fiber was purchased from Suzhou Saifei Group.
[0026] Example 1
[0027] A non-metallic high-temperature resistant temperature-sensitive optical cable, the center of the optical cable is a high-temperature resistant optical fiber, and the optical fiber is wrapped from the inside to the outside respectively: a tight cladding, a high-temperature resistant protective component, a high-temperature resistant inner protective layer, and a high-temperature resistant outer sheath.
[0028] The tight cladding is a polyimide composite material; the preparation method of the polyimide composite material is: polyimide, nanographene and nanosilicon dioxide with a mass ratio of 75:2:15 are melt-blended at 320° C. for 30 minutes to obtain the polyimide composite material.
[0029] The high temperature resistant protective part is a polytetrafluoroethylene bellows filled with aluminum silicate aerogel composite material; the preparation method of the polytetrafluoroethylene bellows is: polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate are mixed evenly in a ball mill, added into a screw extruder, melt blended according to the temperature gradient set at 350°C in the feeding section, 340°C in the mixing section and 300°C in the base section, and a bellows with a diameter of 410 μm is extruded through a bellows die; the mass ratio of polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate is 100:15:1.8:1.2;
[0030] The preparation method of the high temperature resistant inner protective layer is as follows: dispersing boron nitride nanotubes and graphene oxide in N-methylpyrrolidone at 40kHz ultrasound for 2h, placing silicon carbide whiskers in a 1wt% silane coupling agent KH550 ethanol solution, adjusting the pH to 8.5 with ammonia water and ultrasonically stirring for 45min, and then washing and drying to obtain modified silicon carbide whiskers, wherein the mass ratio of the silicon carbide whiskers to the silane coupling agent KH550 is 100:1.5; Ether ketone, polyimide, boron nitride nanotubes, graphene oxide, N-methyl pyrrolidone and modified silicon carbide whiskers are added into a twin-screw extruder, and the feeding section temperature is set to 340°C, the mixing section temperature is set to 380°C, and the extrusion section temperature is set to 360°C to obtain a high-temperature resistant inner protective layer material; the mass ratio of polyether ether ketone, polyimide, boron nitride nanotubes, graphene oxide, N-methyl pyrrolidone and modified silicon carbide whiskers is 6.5:3.5:3:1:8:8.
[0031] The high temperature resistant outer sheath is woven from aramid, modified silicon carbide fiber and polytetrafluoroethylene fiber. The preparation method of the modified silicon carbide fiber is as follows: immersing the silicon carbide fiber in a 1.5% silane coupling agent KH550 anhydrous ethanol solution, ultrasonicating at 40°C for 45 minutes, drying at 100°C for 12 hours, and further heat treating at 180°C for 45 minutes.
[0032] The preparation of the non-metallic high temperature resistant temperature sensitive optical cable comprises the following steps:
[0033] (1) A modified polyimide coating with a thickness of 50 μm was applied to a high temperature resistant optical fiber with a diameter of 250 μm, a wavelength of 365 nm, and an intensity of 500 mJ / cm 2 The ultraviolet curing treatment forms a tight cladding optical fiber;
[0034] (2) Passing a tight-clad optical fiber through a corrugated tube, injecting an aluminum silicate gel composite material, treating it at a vacuum negative pressure of -0.08 MPa for 25 minutes to eliminate internal bubbles, placing it in a supercritical drying device, using liquid carbon dioxide as a drying medium, setting the temperature to 40°C, the pressure to 10 MPa, and drying it for 24 hours to obtain a corrugated tube high-temperature resistant protective part of aluminum silicate aerogel with a nanoporous structure;
[0035] (3) Put the high temperature resistant inner protective layer material into the extruder, set the feeding section temperature to 340°C, the mixing section temperature to 380°C, and the extrusion section temperature to 360°C, and evenly coat the inner protective layer material on the outside of the high temperature resistant protective part to form a complete high temperature resistant inner protective layer with a moderate thickness of 0.8 mm;
[0036] (4) Aramid, modified silicon carbide fiber, and polytetrafluoroethylene fiber are three-dimensionally woven in a mass ratio of 6:3:1, with a braiding angle of 58° and a braiding density of 120 strands / inch to form a high-temperature resistant outer sheath that is coated on the outer surface of the inner sheath to obtain a non-metallic high-temperature resistant temperature-sensitive optical cable.
[0037] The preparation method of the aluminum silicate gel composite material in step (2) is as follows: dissolving aluminum nitrate and sodium silicate in deionized water, adjusting the pH value to 4 with 1M dilute hydrochloric acid, stirring at 70°C for 3 hours to form a uniform aluminum silicate sol, adding ammonia catalyst to the sol, adjusting the pH value to 7, promoting the transformation of the sol to gel, standing for 22 hours to gel the sol, immersing the gel in anhydrous ethanol for 10 hours and performing solution replacement 4 times to obtain the aluminum silicate gel composite material; the mass ratio of the aluminum nitrate, sodium silicate and deionized water is 1.8:1.2:25.
[0038] Example 2
[0039] A non-metallic high-temperature resistant temperature-sensitive optical cable, the center of the optical cable is a high-temperature resistant optical fiber, and the optical fiber is wrapped from the inside to the outside respectively: a tight cladding, a high-temperature resistant protective component, a high-temperature resistant inner protective layer, and a high-temperature resistant outer sheath.
[0040] The tight cladding is a polyimide composite material; the preparation method of the polyimide composite material is: polyimide, nanographene and nanosilicon dioxide with a mass ratio of 70:1:10 are melt-blended at 300° C. for 20 minutes to obtain the polyimide composite material.
[0041] The high temperature resistant protective part is a polytetrafluoroethylene bellows filled with aluminum silicate aerogel composite material; the preparation method of the polytetrafluoroethylene bellows is: polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate are mixed evenly in a ball mill, added into a screw extruder, and melt blended according to the temperature gradient set at 340°C in the feeding section, 330°C in the mixing section, and 290°C in the base section, and a bellows with a diameter of 400 μm is extruded through a bellows die; the mass ratio of polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate is 100:10:1.6:1;
[0042] The preparation method of the high temperature resistant inner protective layer comprises: dispersing boron nitride nanotubes and graphene oxide in N-methylpyrrolidone at 35-45kHz ultrasound for 1 hour, placing silicon carbide whiskers in 0.5wt% silane coupling agent KH550 ethanol solution, adjusting the pH to 8 with ammonia water, ultrasonically stirring for 30 minutes, and washing and drying to obtain modified silicon carbide whiskers; mixing polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidinone, Alkyl ketone and modified silicon carbide whiskers are added into a twin-screw extruder, and the feeding section temperature is set to 330°C, the mixing section temperature is set to 370°C, and the extrusion section temperature is set to 350°C to obtain a high-temperature resistant inner protective layer material, wherein the mass ratio of the silicon carbide whiskers to the silane coupling agent KH550 is 100:1; the mass ratio of the polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers is 6:3:1:0.5:5:5.
[0043] The high temperature resistant outer sheath is woven from aramid, modified silicon carbide fiber and polytetrafluoroethylene fiber. The preparation method of the modified silicon carbide fiber is as follows: the silicon carbide fiber is immersed in a 1% silane coupling agent KH550 anhydrous ethanol solution, ultrasonicated at 30°C for 30 minutes, then dried at 80°C for 10 hours, and further heat treated at 150°C for 30 minutes.
[0044] The preparation of the non-metallic high temperature resistant temperature sensitive optical cable comprises the following steps:
[0045] (1) A modified polyimide coating with a thickness of 45 μm was applied to a high temperature resistant optical fiber with a diameter of 250 μm, a wavelength of 365 nm, and an intensity of 500 mJ / cm 2 The ultraviolet curing treatment forms a tight cladding optical fiber;
[0046] (2) Passing a tight-clad optical fiber through a corrugated tube, injecting an aluminum silicate gel composite material, treating it at a vacuum negative pressure of -0.08 MPa for 20 minutes to eliminate internal bubbles, placing it in a supercritical drying device, using liquid carbon dioxide as a drying medium, setting the temperature to 35°C, the pressure to 8 MPa, and drying it for 22 hours to obtain a corrugated tube high-temperature resistant protective part of aluminum silicate aerogel with a nanoporous structure;
[0047] (3) Put the high temperature resistant inner protective layer material into the extruder, set the feeding section temperature to 330°C, the mixing section temperature to 370°C, and the extrusion section temperature to 350°C, and evenly coat the inner protective layer material on the outside of the high temperature resistant protective part to form a complete high temperature resistant inner protective layer with a moderate thickness of 0.5 mm;
[0048] (4) Aramid, modified silicon carbide fiber, and polytetrafluoroethylene fiber are three-dimensionally woven in a mass ratio of 5:2:0.5, with a braiding angle of 56° and a braiding density of 115 strands / inch to form a high-temperature resistant outer sheath that is coated on the outer surface of the inner sheath to obtain a non-metallic high-temperature resistant temperature-sensitive optical cable.
[0049] The preparation method of the aluminum silicate gel composite material in step (2) is as follows: dissolving aluminum nitrate and sodium silicate in deionized water, adjusting the pH value to 3 with 1M dilute hydrochloric acid, stirring at 60°C for 2 hours to form a uniform aluminum silicate sol, adding ammonia catalyst to the sol, adjusting the pH value to 6, promoting the transformation of the sol to gel, standing for 20 hours to gel the sol, immersing the gel in anhydrous ethanol for 8 hours and performing solution replacement 3 times to obtain the aluminum silicate gel composite material; the mass ratio of aluminum nitrate, sodium silicate and deionized water is 1.5:1:20.
[0050] Example 3
[0051] A non-metallic high-temperature resistant temperature-sensitive optical cable, the center of the optical cable is a high-temperature resistant optical fiber, and the optical fiber is wrapped from the inside to the outside respectively: a tight cladding, a high-temperature resistant protective component, a high-temperature resistant inner protective layer, and a high-temperature resistant outer sheath.
[0052] The tight cladding is a polyimide composite material; the preparation method of the polyimide composite material is: polyimide, nanographene and nanosilicon dioxide with a mass ratio of 80:3:20 are melt-blended at 350° C. for 40 minutes to obtain the polyimide composite material.
[0053] The high temperature resistant protective part is a polytetrafluoroethylene bellows filled with aluminum silicate aerogel composite material; the preparation method of the polytetrafluoroethylene bellows is: polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate are mixed evenly in a ball mill, added into a screw extruder, and melt blended according to the temperature gradient set at 360°C in the feeding section, 350°C in the mixing section, and 310°C in the base section, and a bellows with a diameter of 420 μm is extruded through a bellows die; the mass ratio of polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate is 100:20:2.0:1.4;
[0054] As a preferred technical solution of the present invention, the preparation method of the high temperature resistant inner protective layer is as follows: dispersing boron nitride nanotubes and graphene oxide in N-methylpyrrolidone 35-45kHz ultrasound for 3h, placing silicon carbide whiskers in a 2wt% silane coupling agent KH550 ethanol solution, adjusting the pH to 9 with ammonia water and ultrasonically stirring for 60min, and then washing and drying to obtain modified silicon carbide whiskers, wherein the mass ratio of the silicon carbide whiskers to the silane coupling agent KH550 is 1:1. 00:2; add polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers into a twin-screw extruder, set the feeding section temperature to 350°C, the mixing section temperature to 390°C, and the extrusion section temperature to 370°C to obtain a high-temperature resistant inner protective layer material; the mass ratio of polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers is 7:4:5:2:10:10.
[0055] The high temperature resistant outer sheath is woven from aramid, modified silicon carbide fiber and polytetrafluoroethylene fiber. The preparation method of the modified silicon carbide fiber is as follows: immersing the silicon carbide fiber in a 2% silane coupling agent KH550 anhydrous ethanol solution, ultrasonicating at 50°C for 60 minutes, drying at 120°C for 10-14 hours, and further heat treating at 200°C for 60 minutes.
[0056] The preparation of the non-metallic high temperature resistant temperature sensitive optical cable comprises the following steps:
[0057] (1) A modified polyimide coating with a thickness of 55 μm was applied to a high temperature resistant optical fiber with a diameter of 250 μm, a wavelength of 365 nm, and an intensity of 500 mJ / cm 2 The ultraviolet curing treatment forms a tight cladding optical fiber;
[0058] (2) Passing a tight-clad optical fiber through a corrugated tube, injecting an aluminum silicate gel composite material, treating it at a vacuum negative pressure of -0.08 MPa for 30 minutes to eliminate internal bubbles, placing it in a supercritical drying device, using liquid carbon dioxide as a drying medium, setting the temperature to 45°C, the pressure to 12 MPa, and drying it for 26 hours to obtain a corrugated tube high-temperature resistant protective part of aluminum silicate aerogel with a nanoporous structure;
[0059] (3) Put the high temperature resistant inner protective layer material into the extruder, set the feeding section temperature to 350°C, the mixing section temperature to 390°C, and the extrusion section temperature to 370°C, and evenly coat the inner protective layer material on the outside of the high temperature resistant protective part to form a complete high temperature resistant inner protective layer with a moderate thickness of 1 mm;
[0060] (4) Aramid fiber, modified silicon carbide fiber, and polytetrafluoroethylene fiber are three-dimensionally woven in a mass ratio of 7:4:1.5, with a braiding angle of 60° and a braiding density of 125 strands / inch to form a high-temperature resistant outer sheath that is coated on the outer surface of the inner sheath to obtain a non-metallic high-temperature resistant temperature-sensitive optical cable.
[0061] The preparation method of the aluminum silicate gel composite material in step (2) is as follows: dissolving aluminum nitrate and sodium silicate in deionized water, adjusting the pH value to 5 with 1M dilute hydrochloric acid, stirring at 80°C for 4 hours to form a uniform aluminum silicate sol, adding ammonia catalyst to the sol, adjusting the pH value to 8, promoting the transformation of the sol to gel, standing for 24 hours to gel the sol, immersing the gel in anhydrous ethanol for 12 hours and performing solution replacement 5 times to obtain the aluminum silicate gel composite material; the mass ratio of the aluminum nitrate, sodium silicate and deionized water is 2:1.5:30.
[0062] Example 4
[0063] A non-metallic high-temperature resistant temperature-sensitive optical cable, the center of the optical cable is a high-temperature resistant optical fiber, and the optical fiber is wrapped from the inside to the outside respectively: a tight cladding, a high-temperature resistant protective component, a high-temperature resistant inner protective layer, and a high-temperature resistant outer sheath.
[0064] The tight cladding is a polyimide composite material; the preparation method of the polyimide composite material is: polyimide, nanographene and nanosilicon dioxide with a mass ratio of 80:1:10 are melt-blended at 320° C. for 25 minutes to obtain the polyimide composite material.
[0065] The high temperature resistant protective part is a polytetrafluoroethylene bellows filled with aluminum silicate aerogel composite material; the preparation method of the polytetrafluoroethylene bellows is: polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate are mixed evenly in a ball mill, added into a screw extruder, and melt blended according to the temperature gradient set at 340°C in the feeding section, 350°C in the mixing section, and 290°C in the base section, and a bellows with a diameter of 410 μm is extruded through a bellows die; the mass ratio of polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate is 100:12:1.7:1.3;
[0066] The preparation method of the high temperature resistant inner protective layer comprises: dispersing boron nitride nanotubes and graphene oxide in N-methylpyrrolidone at 38kHz ultrasound for 1 hour, placing silicon carbide whiskers in 0.8wt% silane coupling agent KH550 ethanol solution, adjusting the pH to 9 with ammonia water, ultrasonically stirring for 30-60 minutes, and washing and drying to obtain modified silicon carbide whiskers; mixing polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone, Ketone and modified silicon carbide whiskers are added into a twin-screw extruder, and the feeding section temperature is set to 350°C, the mixing section temperature is set to 370°C, and the extrusion section temperature is set to 350°C to obtain a high-temperature resistant inner protective layer material, wherein the mass ratio of the silicon carbide whiskers to the silane coupling agent KH550 is 100:1.2; the mass ratio of the polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers is 6:3:5:2:10:10.
[0067] The high temperature resistant outer sheath is woven from aramid, modified silicon carbide fiber and polytetrafluoroethylene fiber. The modified silicon carbide fiber is prepared by immersing the silicon carbide fiber in a 2% silane coupling agent KH550 anhydrous ethanol solution, ultrasonicating at 30°C for 60 minutes, drying at 120°C for 10 hours, and further heat treating at 200°C for 33 minutes.
[0068] The preparation of the non-metallic high temperature resistant temperature sensitive optical cable comprises the following steps:
[0069] (1) A modified polyimide coating with a thickness of 52 μm was applied to a high temperature resistant optical fiber with a diameter of 250 μm, a wavelength of 365 nm, and an intensity of 500 mJ / cm 2 The ultraviolet curing treatment forms a tight cladding optical fiber;
[0070] (2) Passing the tight clad optical fiber through the corrugated tube, injecting the aluminum silicate gel composite material, treating it at a vacuum negative pressure of -0.08 MPa for 22 minutes to eliminate internal bubbles, placing it in a supercritical drying device, using liquid carbon dioxide as a drying medium, setting the temperature to 36°C, the pressure to 9 MPa, and drying it for 23 hours to obtain a corrugated tube high temperature resistant protective part of aluminum silicate aerogel with a nanoporous structure;
[0071] (3) Put the high temperature resistant inner protective layer material into the extruder, set the feeding section temperature to 330°C, the mixing section temperature to 390°C, and the extrusion section temperature to 370°C, and evenly coat the inner protective layer material on the outside of the high temperature resistant protective part to form a complete high temperature resistant inner protective layer with a moderate thickness of 0.7 mm;
[0072] (4) Aramid, modified silicon carbide fiber, and polytetrafluoroethylene fiber are three-dimensionally woven in a mass ratio of 5:4:1.5, with a braiding angle of 59° and a braiding density of 122 strands / inch to form a high-temperature resistant outer sheath that is coated on the outer surface of the inner sheath to obtain a non-metallic high-temperature resistant temperature-sensitive optical cable.
[0073] The preparation method of the aluminum silicate gel composite material in step (2) is as follows: dissolving aluminum nitrate and sodium silicate in deionized water, adjusting the pH value to 3.2 with 1M dilute hydrochloric acid, stirring at 63°C for 3 hours to form a uniform aluminum silicate sol, adding ammonia catalyst to the sol, adjusting the pH value to 6.6, promoting the transformation of the sol to gel, standing for 21 hours to gel the sol, immersing the gel in anhydrous ethanol for 9 hours and performing solution replacement 4 times to obtain the aluminum silicate gel composite material; the mass ratio of the aluminum nitrate, sodium silicate and deionized water is 1.7:1.5:22.
[0074] Comparative Example 1
[0075] On the basis of Example 1, a polyimide composite material was prepared without adding nano-graphene, and the mass ratio of polyimide to nano-silicon dioxide was changed to 75:17. The rest was the same as in Example 1.
[0076] Comparative Example 2
[0077] On the basis of Example 1, a polyimide composite material was prepared without adding nano-silicon dioxide, and the mass ratio of polyimide to nano-graphene was changed to 75:17. The rest was the same as in Example 1.
[0078] Comparative Example 3
[0079] On the basis of Example 1, polyimide is not added to the inner protective layer material, and the mass ratio of polyetheretherketone, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers is changed to 10:3:1:8:8.
[0080] Comparative Example 4
[0081] On the basis of Example 1, no boron nitride nanotubes are added to the inner protective layer material, and the mass ratio of polyetheretherketone, polyimide, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers is changed to 6.5:3.5:4:8:8.
[0082] Comparative Example 5
[0083] On the basis of Example 1, graphene oxide is not added to the inner protective layer material, and the mass ratio of polyetheretherketone, polyimide, boron nitride nanotubes, N-methylpyrrolidone and modified silicon carbide whiskers is changed to 6.5:3.5:1:8:11.
[0084] Comparative Example 6
[0085] On the basis of Example 1, the modified silicon carbide whiskers are not added to the inner protective layer material, and the mass ratio of polyetheretherketone, polyimide, graphene oxide, boron nitride nanotubes and N-methylpyrrolidone is changed to 6.5:3.5:11:1:8.
[0086] Comparative Example 7
[0087] On the basis of Example 1, the high temperature resistant outer sheath does not contain modified silicon carbide fiber, and the mass ratio of aramid fiber to polytetrafluoroethylene fiber is 6:4. The rest is the same as Example 1.
[0088] Performance Test:
[0089] Tensile strength and elongation at break test: according to GB / T2951.11-2008;
[0090] High temperature resistance test: After aging treatment at 200°C for 5 days, the tensile strength and elongation at break were tested according to the above method.
[0091]
[0092] From the test results, it can be seen that the tight sheath of the present invention adopts a polyimide composite material, the inner sheath material is made of high-performance fillers such as composite boron nitride nanotubes, graphene oxide, silicon carbide whiskers, etc., and the outer sheath is three-dimensionally woven by aramid fiber, modified silicon carbide fiber and polytetrafluoroethylene fiber, which significantly increases the high temperature resistance of the optical cable material.
[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A non-metallic high temperature resistant temperature sensitive optical cable, characterized in that: The center of the optical cable is a high temperature resistant optical fiber, and the optical fiber is wrapped from the inside to the outside respectively: a tight cladding, a high temperature resistant protective component, a high temperature resistant inner protective layer, and a high temperature resistant outer sheath.
2. A non-metallic high temperature resistant temperature sensitive optical cable according to claim 1, characterized in that: The tight cladding is a polyimide composite material; the preparation method of the polyimide composite material is: polyimide, nanographene and nanosilicon dioxide with a mass ratio of 70-80:1-3:10-20 are melt-blended at 300-350° C. for 20-40 minutes to obtain the polyimide composite material.
3. The non-metallic high temperature resistant temperature sensitive optical cable according to claim 1, characterized in that: The high temperature resistant protective part is a polytetrafluoroethylene bellows filled with aluminum silicate aerogel composite material; the preparation method of the polytetrafluoroethylene bellows is: polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate are mixed evenly in a ball mill, added into a screw extruder, melt blended according to the temperature gradient set at 340-360°C in the feeding section, 330-350°C in the mixing section, and 290-310°C in the base section, and a bellows with a diameter of 400-420 μm is extruded through a bellows die; the mass ratio of the polytetrafluoroethylene, boron nitride nanosheets, azodicarbonamide and ammonium bicarbonate is 100:10-20:1.6-2.0:1.0-1.
4.
4. The non-metallic high temperature resistant temperature sensitive optical cable according to claim 1, characterized in that: The preparation method of the high temperature resistant inner protective layer is as follows: dispersing boron nitride nanotubes and graphene oxide in N-methylpyrrolidone at 35-45kHz ultrasound for 1-3h, placing silicon carbide whiskers in a 0.5-2wt% silane coupling agent KH550 ethanol solution, adjusting the pH to 8-9 with ammonia water, ultrasonically stirring for 30-60min, and washing and drying to obtain modified silicon carbide whiskers; mixing polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers are added into a twin-screw extruder, and the feeding section temperature is set to 330-350°C, the mixing section temperature is set to 370-390°C, and the extrusion section temperature is set to 350-370°C to obtain a high-temperature resistant inner protective layer material; the mass ratio of the polyetheretherketone, polyimide, boron nitride nanotubes, graphene oxide, N-methylpyrrolidone and modified silicon carbide whiskers is 6-7:3-4:1-5:0.5-2:5-10:5-10.
5. The non-metallic high temperature resistant temperature sensitive optical cable according to claim 1, characterized in that: The high temperature resistant outer sheath is woven from aramid, modified silicon carbide fiber and polytetrafluoroethylene fiber. The preparation method of the modified silicon carbide fiber is as follows: immersing the silicon carbide fiber in a 1-2% silane coupling agent KH550 anhydrous ethanol solution, ultrasonicating at 30-50°C for 30-60min, drying at 80-120°C for 10-14h, and further heat treating at 150-200°C for 30-60min.
6. A preparation method for a non-metallic high temperature resistant temperature sensitive optical cable as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: (1) A modified polyimide coating with a thickness of 50±5μm was applied to a high temperature resistant optical fiber with a diameter of 250um, a wavelength of 365nm, and an intensity of 500mJ / cm 2 The ultraviolet curing treatment forms a tight cladding optical fiber; (2) Passing the tight clad optical fiber through the corrugated tube, injecting the aluminum silicate gel composite material, treating it at a vacuum negative pressure of -0.08 MPa for 20-30 minutes to eliminate internal bubbles, placing it in a supercritical drying device, using liquid carbon dioxide as a drying medium, setting the temperature to 35-45° C., the pressure to 8-12 MPa, and drying it for 22-26 hours to obtain a corrugated tube high temperature resistant protective part of aluminum silicate aerogel with a nanoporous structure; (3) placing the high temperature resistant inner protective layer material into the extruder, setting the feeding section temperature to 330-350°C, the mixing section temperature to 370-390°C, and the extrusion section temperature to 350-370°C, and uniformly coating the inner protective layer material on the outside of the high temperature resistant protective part to form a complete high temperature resistant inner protective layer with a moderate thickness of 0.5-1 mm; (4) Aramid fiber, modified silicon carbide fiber, and polytetrafluoroethylene fiber are three-dimensionally woven in a mass ratio of 5-7:2-4:0.5-1.5, with a braiding angle of 58±2° and a braiding density of 120±5 strands / inch to form a high-temperature resistant outer sheath that is coated on the outer surface of the inner sheath to obtain a non-metallic high-temperature resistant temperature-sensitive optical cable.
7. The preparation of a non-metallic high temperature resistant temperature sensitive optical cable according to claim, characterized in that: The preparation method of the aluminum silicate gel composite material in step (2) is as follows: dissolving aluminum nitrate and sodium silicate in deionized water, adjusting the pH value to 3-5 with 1M dilute hydrochloric acid, stirring at 60-80°C for 2-4 hours to form a uniform aluminum silicate sol, adding ammonia catalyst to the sol, adjusting the pH value to 6-8, promoting the transformation of the sol into a gel, standing for 20-24 hours to gel the sol, immersing the gel in anhydrous ethanol for 8-12 hours and performing solution replacement 3-5 times to obtain the aluminum silicate gel composite material; the mass ratio of the aluminum nitrate, sodium silicate and deionized water is 1.5-2.0:1-1.5:20-30.
Citation Information
Patent Citations
High temperature-resistant light optical cable for aeronautics and astronautics and preparation method
CN106772857A
Optical cable for nuclear power station and preparing method thereof
CN106842465A
Tight sleeving optical cable with high temperature resistance for aerospace
CN204439897U
High temperature resistance optical cable
CN207937659U
Crush-resistant high-strength buffered optical waveguide fiber cable
US5293442A
Cited By
Continuous casting machine cable based on polyimide composite material and preparation method thereof
CN120656781A